A thermally-driven seawater desalination system: Proof of concept and vision for future sustainability. (July 2022) - Alrowais, Raid; Shahzad, Muhammad Wakil; Burhan, Muhammad; Bashir, M.T.; Chen, Qian; Xu, Ben Bin; Kumja, M.; Markides, Christos N.; Ng, Kim Choon
Abstract: Since the 1970s, commercial-scale thermally-driven seawater desalination plants have been powered by low-grade energy sources, drawn either with low-pressure bled-steam from steam turbines or the solar renewable energy harvested that are supplied at relatively low temperatures. Despite the increasing trend of seawater reverse osmosis plants, the role of thermal desalination methods (such as multi-stage flashing and multi-effect distillation) in GCC countries is still relevant in the Arabian Gulf, arising from higher salinity, the frequent algae blooms of seawater and their ability to utilize low temperature heat sources. Given the urgent need for lowering both the capital and operating costs of all processes within the desalination industry and better thermodynamic adaptation of low-grade heat input from renewable sources, the present paper addresses the abovementioned issues by investigating the direct contact spray evaporation and condensation (DCSEC) method. A DCSEC system comprises only hollow chambers (devoid of membranes or tubes, minimal use of chemical and maintenance) where vapor generation (flashing) utilizes the enthalpy difference between the sprayed feed seawater and the saturated vapor enthalpy of the vessels. Concomitantly, vapor is condensed with spray droplets of cooler water (potable) in adjacent condenser vessels, employing a simple design concept. We present detailed design and real seawater experiments data of a DCSEC system for the first time. The water production cost is calculated as $0.52/m 3, which is one of the lowest figures reported compared to commercial processes presented by Global Water Intelligence.